Respiratory failure due to tracheobronchomalacia. Issue 2 (February 1996) - Collard, P.; Freitag, L.; Reynaert, M. S.; Rodenstein, D. O.; Francis, C.
Abstract : A case is described of tracheobronchomegaly progressing to extensive tracheomalacia, complicated by episodic choking, recurrent pulmonary infections, and irreversible hypercapnic respiratory failure. A Y-shaped tracheobronchial stent was placed endoscopically to splint the trachea open, with excellent clinical and physiological improvement. New stent designs may provide long term palliation in selected cases of diffuse tracheal collapse or stenosis, and offer an alternative to surgical repair.